PECULIARITIES OF ROD PRODUCTION OUT OF LOW-ALLOYED STEEL ON THE MILL 150 - V. I. Shcherbakov; V. I. Ibragimov; V. V. Savinkov (Литьë и металлургия, 2006)
The technical agreements are developed for production of steel at the mill 150.